PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN - Diah Nurriza Indah Permata; Fariyana Kusumawati; Rindah F. Suryawati (Universitas Trunojoyo Madura, 2012)
Since the economic crisis 1997 the implementation of good corporate governance has become a big issue in Indonesia. It has been discussed among government and practitioners that economic recovery needs to be supported by implementing good corporate governance. The purpose of this research is to investigate the influence of Good Corporate Governance practices to the company's financial performance. The independent variable in this research is the implementation of GCG and the dependent variable is the financial performance measured by ratio of liquidity, profitability, leverage, activity, and markets. The sample consisted of 45 companies included in the top 10 rankings Corporate Governance Perception Index (CGPI) period 2007-2011 which has the GCG score of more than 80 CGPI (80). To test the hypothesis, it was used a simple linear regression and t tests method. The result of this research suggests that the implementation of GCG gives the significance influence on the company financial performance measured by ratio of liquidity, leverage, activity, and markets. But the implementation of GCG doesn’t influent significantly on the financial performance company that is measured by profitability ratio.